The "Natural" History of Medically Treated Temporal Lobe Epilepsy: What Can an Evidence-Based Approach Tell Us?. (16th February 2012) - Josephson, Colin Bruce; Pohlmann-Eden, Bernhard
Abstract : We systematically reviewed the literature to describe the "natural" history of medically treated temporal lobe epilepsy (TLE). No population-based studies recruiting incident cases of TLE irrespective of age exist. Prospective, population-based studies were limited to those recruiting only childhood-onset TLE or those reporting TLE as a subgroup of cohorts of focal epilepsies. Few studies have been performed in the "MRI era" limiting information on natural history secondary to specific pathologies. Available data suggests that TLE is highly variable, with unpredictable transient remissions and low rates of seizure freedom (30 to 50%). Etiology and failure of first and second drug seem to be the most important predictors for treatment prognosis. The role of initial precipitating injuries remains speculative, as imaging information of related events is either missing or conflicting. Prospective cohorts of new-onset TLE with long-term followup using advanced MRI techniques, timely EEG recordings, and assessments of psychiatric comorbidities are needed.